2013
DOI: 10.1155/2013/134656
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Characterization of Oak Extracts Combining Spectrophotometric Assays and Chemometrics

Abstract: Antioxidant characteristics of leaves, twigs, and acorns from two Serbian oak species Quercus robur L. and Quercus petraea L. from Vojvodina province (northern Serbia) were investigated. 80% ethanol (in water) extracts were used for antiradical power (ARP) determinations against DPPH•, •NO, and O2 •− radicals, ferric reducing antioxidant power (FRAP), total phenol, tannin, flavonoid, and proanthocyanidin contents. Permanganate reducing antioxidant capacity (PRAC) was determined using water extracts. Beside, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 44 publications
(47 reference statements)
4
36
0
Order By: Relevance
“…Previous studies confirmed these differences indicating that the presence of polyphenolic compounds is negatively correlated with the antioxidant activities (36). It has been shown that the principle component is the main contributor to the causal effect (37). In this study, the tocopherol content had correlation values with antioxidant activity of R 2 =0.545 and 0.867 with maximum values for inhibition of the peroxyl radical and for expression of anti-inflammatory activities in vitro.…”
Section: Resultssupporting
confidence: 78%
“…Previous studies confirmed these differences indicating that the presence of polyphenolic compounds is negatively correlated with the antioxidant activities (36). It has been shown that the principle component is the main contributor to the causal effect (37). In this study, the tocopherol content had correlation values with antioxidant activity of R 2 =0.545 and 0.867 with maximum values for inhibition of the peroxyl radical and for expression of anti-inflammatory activities in vitro.…”
Section: Resultssupporting
confidence: 78%
“…Catalase content in poultry in trial groups was higher than in control by 45.3-71.9 % (Р  0.05). Antioxidant properties of oak bark extracts [22,23] are also shown in our tests. Increased total antioxidant activity and SOD level in blood of broilers [24,25] were due to feed supplementation with gallic acid, an oak bark component.…”
Section: Introductionsupporting
confidence: 75%
“…Santos et al [29] noted that cork of Quercus super obtained 2.4 -10.6 mg GAE/g DW while twigs and acorns extracts of Quercus robur and Quercus petraea showed 7.44 and 16.25 mg catechin/g DW respectively. Other reports included the total phenolic contents in leaf extracts of Q. robur and Q. petraea ranged from 32 -35 mg catechin/g DW [30] and Quercus resinosa, Quercus laeta, and Quercus obtusata (5.7 -7.1 mg GAE/g DW) [31]. In addition, total phenolic contents in leaf and bark extracts of Q. salicina were higher than some medicinal plants in previous studies such as Aristolochia mollissima, Lobelia chinensis, Dianthus superbus and Centipeda minima (3.9 -5.9 mg/g DW) [32].…”
Section: Discussionmentioning
confidence: 99%